Light–Matter Interaction in Quantum Confined 2D Polar Metals. (15th October 2020) - Nisi, Katharina; Subramanian, Shruti; He, Wen; Ulman, Kanchan Ajit; El‐Sherif, Hesham; Sigger, Florian; Lassaunière, Margaux; Wetherington, Maxwell T.; Briggs, Natalie; Gray, Jennifer; Holleitner, Alexander W.; Bassim, Nabil; et al.
Abstract: This work is a systematic experimental and theoretical study of the in‐plane dielectric functions of 2D gallium and indium films consisting of two or three atomic metal layers confined between silicon carbide and graphene with a corresponding bonding gradient from covalent to metallic to van der Waals type. k ‐space resolved free electron and bound electron contributions to the optical response are identified, with the latter pointing towards the existence of thickness dependent quantum confinement phenomena. The resonance energies in the dielectric functions and the observed epsilon near‐zero behavior in the near infrared to visible spectral range, are dependent on the number of atomic metal layers and properties of the metal involved. A model‐based spectroscopic ellipsometry approach is used to estimate the number of atomic metal layers, providing a convenient route over expensive invasive characterization techniques. A strong thickness and metal choice dependence of the light–matter interaction makes these half van der Waals 2D polar metals attractive for quantum engineered metal films, tunable (quantum‐)plasmonics and nano‐photonics. Abstract : A systematic experimental and theoretical study of the in‐plane dielectric functions of 2D gallium and indium films consisting of two or three atomic metal layers shows a strong thickness and metal choice dependence of the light–matter interaction and epsilon near‐zero properties, making these 2D polar metals attractive for quantum engineered metal films, tunable (quantum‐)plasmonics, and nanophotonics.